Heroin policy and deficit models: the limits of Left Realism - Mugford, Stephen K. (Crime, law and social change, 1991)
This paper critically assesses Left Realist approaches to understanding heroin use and to formulating policies with which to deal with heroin use as a social problem. It criticises the epistemological foundation of Left Realism, querying especially its prioritizing of inner city residents' experiences. Dorn and South's Left Realist account of heroin use and their formulation of an appropriate policy are then argued to have fundamental weaknesses as a result of their Left Realist assumptions. The paper then attempts to indicate some alternative paradigms for interpreting drug use, developing especially a focus on theorizing demand, and suggests alternative policy directions which emerge from this. *** DIRECT SUPPORT *** AW502012 00003